2021
DOI: 10.3389/fonc.2020.600980
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma Cells Produce Their Own Extracellular Matrix With Minimal Involvement of Cancer-Associated Fibroblasts: A Preliminary Study

Abstract: BackgroundThe interplay between neoplastic cells and surrounding extracellular matrix (ECM) is one of the determinant elements for cancer growth. The remodeling of the ECM by cancer-associated fibroblasts (CAFs) shapes tumor microenvironment by depositing and digesting ECM proteins, hence promoting tumor growth and invasion. While for epithelial tumors CAFs are well characterized, little is known about the stroma composition of mesenchymal cancers, such as in rhabdomyosarcoma (RMS), the most common soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
(62 reference statements)
0
19
0
1
Order By: Relevance
“…Patients with collagen-rich stroma tumors are typically at higher risk of metastasis and this combination creates barriers to systemic radiotherapy and chemotherapy by promoting tumor invasion. 31 Our study showed that ADC and D values were significantly correlated with stromal fraction in a mouse model of RMS. The tumor stroma produced abundant collagen fibers, which could be a major barrier to water molecule diffusion.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Patients with collagen-rich stroma tumors are typically at higher risk of metastasis and this combination creates barriers to systemic radiotherapy and chemotherapy by promoting tumor invasion. 31 Our study showed that ADC and D values were significantly correlated with stromal fraction in a mouse model of RMS. The tumor stroma produced abundant collagen fibers, which could be a major barrier to water molecule diffusion.…”
Section: Discussionmentioning
confidence: 48%
“…The mechanism of tumor–stroma interaction is of therapeutic importance. Patients with collagen‐rich stroma tumors are typically at higher risk of metastasis and this combination creates barriers to systemic radiotherapy and chemotherapy by promoting tumor invasion 31 . Our study showed that ADC and D values were significantly correlated with stromal fraction in a mouse model of RMS.…”
Section: Discussionmentioning
confidence: 52%
“…In STS, the cell types responsible for aberrant ECM deposition have not been conclusively identified, but studies of subtypes such as undifferentiated pleomorphic sarcoma and rhabdomyosarcoma suggest that sarcoma cells themselves may be culpable [49,52]. This phenomenon has been more extensively studied in epithelial tumors, where, unlike in sarcomas, cancer-associated fibroblasts (CAFs) have been implicated as the primary source of matrix proteins in the TME.…”
Section: Context Matters: Individual Collagensmentioning
confidence: 99%
“…GFP + RH30 were kindly provided by Dr Rampazzo. 26 Integrin alpha 5-negative RH30 cells (ITGA5 − RH30) were obtained using ITGA5 siRNA (Santa Cruz Biotechnology, Dallas, Texas, USA) and Mirus TransIT-X2 Transfection Reagent (Mirus Bio, Wisconsin, USA) following the manufacturer's instructions. As a control a siRNA scramble sequence (siNEG, Santa Cruz Biotechnology, Dallas, Texas, USA) was used.…”
Section: Cell Culture and Spheroid Formationmentioning
confidence: 99%
“…Trans-wells with coating solution were kept in the incubator for 1 hour) as described elsewhere. 26 Briefly, 1 × 10 5 cancer cells were seeded in the upper chamber, and the lower chamber was filled with serumfree medium. After 24 h, membranes were fixed in 4% PFA and stained with 1 : 10 000 Hoechst solution (Life Technologies, Carlsbad, California, USA) for 15 minutes.…”
Section: Cell Migration and Invasion Testmentioning
confidence: 99%